Pendidikan Karakter Bagi Generasi Z - Andra Ardianda Prasetyo (Universitas 45 Surabaya, 2023)
To influence the teaching and learning process, either through media, visual aids, learning resources, or other means, technological advances are currently increasingly sophisticated. The professional role of school principals and teachers in preparing Generation Z students is greatly affected by this. This research method uses rivew literature. Sources for this research were obtained from journal articles, books, and other documentation that explained theory and knowledge. The results of this study need character education for Generation Z due to the lack of mature characters.